Classical Guitar Learning At Gracia Music Course Kediri - Ega Putra A.I.M; Setyo Yanuartuti (PT. Anagata Sembagi Education, 2024)
This study aims to describe the background of Gracia Music Course, the classical guitar learning process conducted, the teaching methods applied by the instructor, and the assessment system in place. This research uses a descriptive qualitative method with the object of the study being classical guitar learning at Gracia Music Course, specifically grade 2 attended by Garvin with instructor Paulus Rudy. The research was conducted at Perumahan Puri Indah Blok A No. 01, Pare, Kediri. Primary data sources were obtained from the founder and instructor, while secondary data included documents and digital references. Data was collected through observation, interviews, and documentation, and then analyzed using data collection, reduction, presentation, and conclusion techniques. The results show that Gracia Music Course was established to provide quality music education with a focus on classical instruments. The learning process is systematically and structurally designed, encompassing preliminary, core, and closing stages. The teaching methods include lectures, demonstrations, Q&A sessions, and drills. Evaluation is conducted on a micro scale at each meeting and on a macro scale every two months through grade advancement exams. The assessment system covers cognitive, affective, and psychomotor aspects to ensure students' mastery of the material.